A new technique for recovering aged mineral oil to promote lifetime and sustainability - Sarathkumar, D.; Montanari, Gian Carlo; Sarathi, R.; Srinivasan, M.; Karthik, R.; Sivadasan, J. (Frontiers in Materials, 2023)
Using mineral oil (MO) derived from petroleum, e.g., transformer insulation, raises environmental risk and affects sustainability. Due to its affordability and easy availability, MO will ineluctably be preferred over other biodegradable oils. Therefore, tools must be developed to recover aged MO, extend the life cycle, and increase its sustainability. The work presented here is aimed at the investigation of the electrical insulation properties of thermally-aged recovered-aged mineral oil (RAMO), as well as of aged cellulose pressboard impregnated by fresh mineral oil (FMO), aged mineral oil (AMO), and RAMO. The AMO is recovered using the combined adsorbents, A* and B*, which are Chitosan-activated Bentonite (CTN-aB) and Polyaniline coated Kapok Fibre (PANI-c-KPF) mix. According to FTIR, the recovered oil, RAMO, displays less C=C double bonds and carbonyl vibrations at 140°C, indicating lower oil ageing compared to AMO. The distribution of the crystalline and amorphous peaks is uniform for aged oil-impregnated pressboard (PB) with FMO and RAMO. Overall, it has been discovered that PB is impregnated with RAMO, resulting in an extended lifetime for the solid insulation. As a result, the increase in emissions slows down, and global sustainability targets are met.